Harry The Dirty Dog - Gene Zion
Harry is a black and white dog who hates having a bath - so when he sees his owner with the dredded bath, he runs away. But in the end, harry gets so dirty that his owners dont recognise him and so he has to beg for the thing he used to dread so much so they let him back into the houshold.